New data on the genus Chrysotoxum Meigen (Diptera: Syrphidae) from North-East Turkey, Armenia, Azerbaijan and Iran including descriptions of three new species. Issue 3 (3rd July 2017) - Vujić, Ante; Nedeljković, Zorica; Hayat, Rüstem; Demirözer, Ozan; Mengual, Ximo; Kazerani, Farzaneh
Abstract : New data and records of the genus Chrysotoxum Meigen, 1803 are reported, arising from taxonomic and faunistic examination of adult specimens collected from 1920 to 2011 from four northeastern provinces of Turkey (Erzurum, Bayburt, Kars, and Artvin), and from the neighboring countries of Armenia, Azerbaijan and Iran. Three new species are described: Chrysotoxum antennalis Vujić, Nedeljković & Hayat sp. n., C. clausseni Vujić, Nedeljković & Hayat sp. n. and C. persicum Vujić, Nedeljković & Hayat sp. n. The first two are known only from northeastern Turkey, and the third also occurs in Armenia, Azerbaijan and Iran. These new species have in common an antenna with the basoflagellomere being shorter than the scape and pedicel together. http://www.zoobank.org/urn:lsid:zoobank.org:pub:4C264678-8E47-4DE0-AC7D-91DABC597BCD